Effect of Chronic Administration of Methanol Extract of Moringa Oleifera on Some Biochemical Indices in Female Wistar Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: The study was conducted to investigate safety associated with prolonged consumption of Moringa oleifera leaves as beverage. Fourteen rats were used in this study. They were divided into 2 groups each containing 7 rats. Rats in group I received 2ml/kg of corn oil (standard vehicle drug). Animals in groups II were administered with 400mg/kg body of methanolic extract of Moringa oleifera (MEMO) for five weeks respectively. Serum collected was analyzed for alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein, albumin, globulin, blood urea nitrogen (BUN) and creatinine. There was significant (P
Keywords: Moringa oleifera; toxicity; hepatic damage; kidney